(untitled) (International Seven Journal of Multidisciplinary, 2025)
The present article analyzes public health as an essential component of social security in Brazil, reflecting on its historical, normative, and social dimensions. It begins with the understanding of social security as an integrated system that seeks to ensure well-being and social protection through health, social insurance, and social assistance. Health is treated here as a fundamental and universal right, constitutionally recognized, and as a structuring element for the realization of citizenship. The study discusses the role of the Unified Health System (SUS) as a central public policy for promoting equity, universality, and comprehensiveness in health care, highlighting the advances and limitations of its implementation. Based on a critical review of the literature and normative frameworks, the article analyzes the contradictions between the universal right to health and the challenges imposed by social inequalities, underfunding, and the growing influence of the private sector. The article also presents reflections on contemporary challenges, such as population aging, the expansion of service coverage, the impacts of health crises, and the social and economic transformations affecting public health in Brazil. It concludes that strengthening public health is imperative to ensure social justice and the effectiveness of social security.